What can an intern of psychology do at school? Discussing the practice and professional education - Naiana Dapieve Patias; Josiane Lieberknecht Wathier Abaid (Universidade Federal de Santa Maria, 2014)
School psychology is dedicated to integrate actions that can facilitate the process of learning and development of scholar community. The psychologist has the function of reviewing his or her own professional concepts and practices constantly so that he or she can deal with the complexity of this reality, broadening the concept of school complaints in order to identify other factors associated with these complaints. This paper presents a report on the interventions done during an internship of school psychology at an Elementary School in the countryside of RS. It was noticed an initial necessity of awareness about the psychologist role and about a greateracceptance of a job that could not be just clinical. The practice of the psychologist and of the psychology intern in this context were discussed and related to education and health in a broad sense.